Matchmaking Strategies for Marital Success: A Case Study of Nurul Hikmah Islamic Boarding School in Tegal, Indonesia - M. Aska Askia; Muhamad Towil Akhirudin (Cv. Kayaswara, Indonesia, 2025)
The practice of matchmaking at Nurul Hikmah Islamic Boarding School in Tuwel, Tegal, constitutes a distinctive socio-religious tradition that warrants scholarly examination, as it involves not only the prospective couple but also the active participation of the Kyai (Islamic religious leader) and parents in facilitating marital success. This study aims to analyze matchmaking strategies and their influence on marital success at Nurul Hikmah Islamic Boarding School. A qualitative case study approach was employed, with data collected through in-depth interviews, participant observation, and document analysis, involving nine purposively selected informants comprising Masayikh, students, alumni, married couples, and community leaders. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing, with trustworthiness ensured through methodological and source triangulation. The findings reveal that: (1) the matchmaking strategy at Nurul Hikmah Islamic Boarding School is grounded in religious considerations, alignment of life vision, and shared pesantren educational backgrounds, with the Kyai and parents serving as advisors and mediators who ensure couple compatibility (kafa'ah) based on Islamic values; and (2) several interconnected factors, including strong religious commitment, effective communication, family and community support, and the psychological-emotional readiness of the couple influence marital success. This study concludes that matchmaking strategies grounded in Islamic values, coupled with the active involvement of the Kyai and parents, can foster harmonious, spiritually blessed marriages characterized by sakinah, mawaddah, and warahmah.